Understanding the current nutritional management for people with amyotrophic lateral sclerosis - A mapping review. (June 2022) - Essat, Munira; Coates, Elizabeth; Clowes, Mark; Beever, Daniel; Hackney, Gemma; White, Sean; Stavroulakis, Theocharis; Halliday, Vanessa; McDermott, Christopher; ,
Summary: Background & aims: Poor nutritional outcomes are observed in people with Amyotrophic Lateral Sclerosis (pwALS) including weight loss and poor dietary intake. Surveys of healthcare professionals have highlighted the lack of evidence and knowledge regarding nutritional management of ALS throughout the disease course. Furthermore, national evidence-based guidance is lacking. This mapping review aims to understand the structure and input of nutritional management services for pwALS. Methods: Systematic searches were conducted across eight electronic databases to identify qualitative and quantitative research on structure and input of nutritional care in ALS. Supplementary searches included grey literature, citation and reference list searching of included studies and key reviews, web searching and contacting experts and organisations that provide ALS services to identify guidelines. Study selection and data extraction were undertaken independently by at least two reviewers. Data was synthesised using a narrative approach. Results: One hundred and nine documents were identified. These consisted of journal articles, guidelines and related documents that contributed evidence towards mapping of nutritional management of pwALS. No evidence on commissioning of nutritional care was identified. Guidelines provided high-level overviews and gave general guidance or recommendations for care; however, these typically focused on gastrostomy with limited guidance on broader aspects, including oral nutrition support. Evidence from primary studies found nutritional care delivery in ALS consisted of multiple types of nutritional management, at different time points during the disease course and involving a range of professionals. There was little evidence relating to proactive nutritional care. Details of healthcare setting, number of professionals involved in care, team composition and how services were delivered in community settings were sparse. Although the role of the speech and language therapist in swallowing assessment and provision of advice on the management of swallowing difficulties was consistent; there was limited evidence on care provided by dietitians. In addition, a small number of studies reported on the use of screening tools. Overall, evidence was consistent that weight management, including monitoring of weight change by professionals and patients, was central and recommended that this should be part of nutritional assessment and follow-up. Conclusions: The evidence identified in this mapping review has highlighted the requirement for further primary research providing specific details on how nutritional management of pwALS is structured and delivered.